Pemanfaatan Aplikasi Berbasis Android Sebagai Solusi Kepedulian Masyarakat Terhadap Sampah di Desa Gunungsari - Alim Citra Aria Bima; Pratiwi Susanti; Puguh Jayadi; Moch Yusuf Asyhari (Yayasan Literasi Sains Indonesia, 2022)
The community and local government waste handling capacity is not optimal. Waste cannot be managed properly, affecting the environment and the surrounding community's health. Garbage is a cultural problem because its impact affects various aspects of life, as is currently happening in the Gunungsari Village environment. When looking at the environmental situation there, it can be seen that residents' awareness of their respective waste segregation is not optimal. It can be seen that only about 20% of residents care and try to take part in waste sorting and 3R management, namely: reduce, reuse and recycle. So seeing these conditions, the community service team took the initiative to provide a K-Trash application technology solution to help villagers' problems in terms of waste management. With the presence of this application, people will become more aware of and understand the complexities of the household waste management process. Some of the community service team's activities in this program include socialization regarding the features, benefits, and purposes of applications used by villagers, providing mass training, and monitoring and evaluating application programs.